DNA-coated gold nanoparticles for the detection of mRNA in live Hydra Vulgaris animals - Moros, M; Kyriazi, M; El-Sagheer, A; Brown, T; Tortiglione, C; Kanaras, A (American Chemical Society, 2018)
Advances in nanoparticle design have led to the development of nanoparticulate systems that can sense intracellular molecules, alter cellular processes, and release drugs to specific targets in vitro. In this work, we demonstrate that oligonucleotide-coated gold nanoparticles are suitable for the detection of mRNA in live Hydra vulgaris, a model organism, without affecting the animal's integrity. We specifically focus on the detection of Hymyc1 mRNA, which is responsible for the regulation of the balance between stem cell self-renewal and differentiation. Myc deregulation is found in more than half of human cancers, thus the ability to detect in vivo related mRNAs through innovative fluorescent systems is of outmost interest.